Pengembangan Mibox Berbasis Gamifikasi Sebagai Alternatif Mengatasi Learning Loss Pada Peserta Didik Tunanetra - Sudarmawan, Warta; Auliya, Ahmad Nur; Pangestu, Yorda Aditya; Antoni, Olivvia; Nurfahrudianto, Aan (Universitas Nusantara PGRI Kediri, 2024)
This research began with the problems of blind students who experienced learning loss during the COVID-19 pandemic. Starting from this problem, there is a need for learning media that can be used by blind students to reduce the danger of learning loss. This research was carried out using an R&D (Research and development) approach, which produced learning media by adapting the method from ADDIE. The aim of this research is to create a learning media, namely the Magical Braille Box (MIBOX) with a gamification method to overcome post-pandemic learning loss. The research results obtained from validation show that the MIBOX application has fulfilled the acceptability aspect of learning media obtained from validation results with assessment results of 80% from material experts, 90% from media experts and 94% from practitioner experts. The average results obtained for the learning media assessment were 88%, which is in the very good category and does not need to be revised. Thus, the results of the data analysis obtained have answered the problem formulation, namely MIBOX has fulfilled the validity aspect to be applied in the learning process at SLB Raharja Sejahtera Kandangan Kediri